Assessment of Environmentally Responsible Health-Oriented Behaviors in Students - safari, Yahya; Yousefpoor, Nasrin (International Journal of Global Health, 2023)
Background & Objective Changing people’s attitude toward the environment is an important approach to the prevention of environmental damages. The present study aimed to evaluate environmentally responsible health-oriented behaviors in students. Materials and Methods This research was performed on 360 medical students (180 males and 180 females) who were selected via stratified random sampling. Data were collected using a responsible environmental behaviors questionnaire. Data analysis was performed in SPSS version 21 using linear regression analysis and Pearson’s correlation-coefficient. Results The scores of the environmental attitude, environmental knowledge, and environmental behaviors of the participants were estimated at 52.63±5.74, 74.43±5.99, and 103.37±11.51, respectively. An insignificant correlation was observed between the environmental knowledge and environmental behaviors of the students (r=0.07; P=0.20). However, the correlation-coefficient between the environmental attitude and environmental behaviors of the students was positive and significant (r=-0.54; P<0.001). A negative, significant correlation was also denoted between the environmental knowledge and environmental attitude of the students (r=-0.39; P<0.001). Conclusion Despite relatively poor environmental awareness and attitude, the majority of the students had proper environmental behaviors. Therefore, it seems that having an environmentally responsible behavior does not rely on environmental attitude and knowledge. In fact, behaviors influenced by social conditions and structure encourage and facilitate environmental behaviors.
Keywords: Environmental Knowledge; Environmental Attitude; Environmental Behavior